2021
DOI: 10.1021/acsanm.1c01862
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Thick SiN Films as Gas Barrier Coatings Densified by Vacuum UV Irradiation

Abstract: Gas barrier films are widely used in electronic and packaging applications. They are also critical components of flexible organic light-emitting diodes (FOLEDs) that require high gas barrier performance. Among the various film manufacturing techniques, solution-processed thin-film encapsulation (TFE) represents a low-cost FOLED fabrication method. The nanometerthick SiN films produced following the vacuum ultraviolet (VUV)-induced densification of solution-processed perhydropolysilazane (PHPS) films in a N 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
3
8
0
Order By: Relevance
“…In fact, the thickness of the PHPS layer decreased by ≈10% after VUV irradiation (12 000 mJ cm −2 ) although it depended on the initial thicknesses of the PHPS layers. [ 42 ] In addition to H 2 release, according to past reports [ 51–53 ] and our findings, [ 42 ] it is also suggested that outgases can be released from the layers, such as NH 3 and PHPS oligomers, during the VUV irradiation process. Thermal desorption spectrometry (TDS), which analyzes the gas molecules released from a layer by heating in a vacuum, was conducted to detect the gas molecules released from the PDSN layers (Figure S5, Supporting Information).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…In fact, the thickness of the PHPS layer decreased by ≈10% after VUV irradiation (12 000 mJ cm −2 ) although it depended on the initial thicknesses of the PHPS layers. [ 42 ] In addition to H 2 release, according to past reports [ 51–53 ] and our findings, [ 42 ] it is also suggested that outgases can be released from the layers, such as NH 3 and PHPS oligomers, during the VUV irradiation process. Thermal desorption spectrometry (TDS), which analyzes the gas molecules released from a layer by heating in a vacuum, was conducted to detect the gas molecules released from the PDSN layers (Figure S5, Supporting Information).…”
Section: Resultssupporting
confidence: 75%
“…The PHPS and PDSN layers were fitted using a single‐layer model with a Gaussian oscillator and a four‐layer model containing SiO 2 at the surface and three single‐layer models, respectively, referring to previous work. [ 42 ] Although the small penetration depth of VUV light owing to the high absorption coefficient in the VUV region of the PHPS layers causes a continuous refractive index distribution in the direction of the layer thickness, the experimental ellipsometric parameters (Ψ and Δ) of the PDSN layers were fitted well by the four‐layer model, as shown in Figure S3a, Supporting Information. The refractive indices of the Top and Mid layers increased as a result of the VUV irradiation, whereas that of the Bot layers almost did not change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the SiO x N y layer, which gradually thickened according to the VUV irradiation time, makes the overall refractive index larger. 39 The thickness reduction of the PHPS layer saturated around 150 nm, confirming a slowdown of the PHPS-to-silica transformation; accordingly, the optimal PHPS curing time was selected as 40 min. We then fabricated multilayer PHPS/PHPS/PET stacks to improve the barrier properties.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The overall refractive index of the PHPS film was increased from 1.54 to 1.67 in accordance with the VUV irradiation time because SiO x N y has a high refractive index of 1.45–1.90. It was observed that the SiO x N y layer, which gradually thickened according to the VUV irradiation time, makes the overall refractive index larger . The thickness reduction of the PHPS layer saturated around 150 nm, confirming a slowdown of the PHPS-to-silica transformation; accordingly, the optimal PHPS curing time was selected as 40 min.…”
Section: Resultsmentioning
confidence: 99%